2020
DOI: 10.1007/s13596-020-00484-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic and anti-hyperglycaemic activity of Tabernanthe iboga aqueous extract in fructose-fed streptozotocin type 2 diabetic rats

Abstract: Root bark preparations of the Gabonese plant Tabernanthe iboga (T. iboga) has long been used in traditional medicine in Central and West African regions for the management of type 2 diabetes (T2D). This study is the first investigation of in vivo hypoglycaemic activity in healthy rats and anti-hyperglycaemic activity of T. iboga in a 10% fructose-fed (40 mg/kg (i.p.) streptozotocin (STZ) injected type 2 diabetic rat model.T. iboga at 50 to 200 mg/kg induced hypoglycaemia activity over 3 hours fasted glucose to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Similarly, Bading-Taïka et al also showed that T. iboga aqueous extract (50 to 200 mg/kg p.o.) had a hypoglycemic impact on healthy rats [78]. This effect was delayed and only manifested after 3 h, which may be indicative of the intracellular action of the compound as previously demonstrated in isolated pancreatic β-cells by Souza et al [79].…”
Section: Tabernanthe Ibogasupporting
confidence: 64%
See 2 more Smart Citations
“…Similarly, Bading-Taïka et al also showed that T. iboga aqueous extract (50 to 200 mg/kg p.o.) had a hypoglycemic impact on healthy rats [78]. This effect was delayed and only manifested after 3 h, which may be indicative of the intracellular action of the compound as previously demonstrated in isolated pancreatic β-cells by Souza et al [79].…”
Section: Tabernanthe Ibogasupporting
confidence: 64%
“…This effect was delayed and only manifested after 3 h, which may be indicative of the intracellular action of the compound as previously demonstrated in isolated pancreatic β-cells by Souza et al [79]. Additionally, T. iboga aqueous extract showed antihyperglycemic effects on non-fasted and fasted blood glucose in fructose-fed STZ diabetic rats [78].…”
Section: Tabernanthe Ibogasupporting
confidence: 64%
See 1 more Smart Citation
“…Another represented that a higher casualty of T2D is connected with lower HDL cholesterol levels [ 17 , 18 ], and smoking cigarettes is also linked to lower HDL cholesterol levels [ 19 , 20 ]. In addition, increased (triglycerides) TG levels were found to be substantially linked to the development of T2D [ 21 , 22 ], whether smoking helps increases triglycerides [ 23 ].…”
Section: Introductionmentioning
confidence: 99%